A study of Chinese university EFL learners’ foreign language listening anxiety, listening strategy use and academic listening performance - Liu, Meihua; Thondhlana, Juliet (Yayasan Obor Indonesia, 2015)
The present study examined foreign language (FL) listening anxiety and listening strategy use in relation to the FL listening comprehension performance of 1702 undergraduate EFL learners from 5 universities in China. The findings were: (1) more than half of the students generally did not feel anxious when listening to English, were low in English listening proficiency, and were not confident in or satisfied with their English listening proficiency, and usually moderately used different types of strategies when listening to English; (2) compared with their female counterparts, the male students felt significantly more anxious when facing listening activities and less satisfied with their English listening proficiency, used significantly more often the memory/attention/understanding-related strategies and were less proficient in English, employed significantly more often‘less active listener strategies’ (FLLSUS6), but significantly less frequently the strategies of negotiation for meaning (FLLSUS1), maintaining fluency (FLLSUS2), getting the gist (FLLSUS4), and nonverbal strategies (FLLSUS5), (3) all FLLAS and FLLSUS scales were highly significantly correlated with each other and the students’ listening comprehension performance, and (4) FLLSUS6, FLLAS2, FLLAS3, FLLAS1, FLLSUS2, and FLLSUS1 were good predictors of English listening comprehension performance. Based on the findings, some discussions are made.